A gênese da preservação do patrimônio em Belo Horizonte: movimentos sociais e a defesa da Praça da Estação - Andre de Sousa Miranda (2007)
This work analyzes the rise of social movements of preservation of the historical patrimony of the city of Belo Horizonte in between the decades of 1970 and 1980. We use as a reference the work of the Brazilian Institute of Architects in the State of Minas Gerais (IAB-MG), which organized the First Meeting for the Revitalization of the Praça da Estação (Railway Station City Square) in 1981. We first analyze three social movements that occurred in Belo Horizonte in this period: the students movement, the environmental protection movement and the historical heritage preservation movement; to understand the history of the participation of the IAB-MG in the struggle in favor of historical preservation. In this context, we investigate the concept of preservation of government agencies and how the IAB-MG brought out the civil society to debate the relevance of the Railway Station Square, a space of identity and collective memory of Belo Horizonte. This event emerges in a set of urban reforms for the democratization of the country, a very rich and favorable moment for the debate of political rights of the society and for the construction of a democratic nation; where the notion of thediffuse civil rights for the preservation of the patrimony appears as one of the associated flags of the representation of the organized society, in special the IAB-MG. Keywords: History, Cultural Patrimony, IAB, Praça da Estação (Belo Horizonte/